BLA Graduate Tracer Study - Danao, Madonna P. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 10, 2023)
Graduate tracer studies are an essential component of curriculum evaluations in higher education institutions. It serves as an invaluable tool for shedding light on the effectiveness and relevance of educational institutions in preparing their graduates for the challenges of the modern world. This graduate tracer study explores the effectiveness of the Bachelor of Landscape Architecture program in the Philippines with a specific focus on the perspectives of its graduates. Over the course of its 55-year history, this program has contributed significantly to the field of landscape architecture in the country. However, in an era of evolving professional demands and societal changes, it is vital to assess a program's alignment with graduate expectations and career outcomes. The study employed a learner-centered approach, gathering data directly from program alumni to understand their experiences, career trajectories, and perceptions of the program's strengths and weaknesses. By conducting surveys, structured questionnaires, and feedback sessions, this study aims to gain a holistic understanding of the graduates' educational journey, post-graduation experiences, and the program's impact on their professional lives. This study applied descriptive analysis of the data using Tableau and Excel. The result acknowledges the importance of the learner’s perspectives for continuous improvement in higher education, benefits the academic institution and contributes to the ongoing development of the landscape architecture profession in the country.